Fishes and floods: stream ecosystem drivers in the Great Plains - Bertrand, Katie Nicole (Kansas State University, 2007)
Global climate change could lead to less frequent but more severe precipitation events in the Great Plains, altering the hydrologic regimes of streams. It is important to quantify species roles in these dynamic systems, because changes in stream communities are likely to accompany predicted changes in hydrology. The effects of species on ecosystem processes also are limited by the frequency of disturbance, because prairie streams are harsh, nonequilibrium systems characterized by a wide range of disturbances. In particular, frequent floods that reset the ecosystem to an early successional state can override the influence of consumer populations because the availability of resources is too unpredictable to maintain stable populations of those species or because species are absent following the flood. As flood frequency decreases, potential consumer effects may intensify. Using a combination of field and experimental stream mesocosm experiments, I (1) characterized the ecosystem effects of southern redbelly dace (Phoxinus erythrogaster), a grazing minnow, (2) tested the interactive effects of flood frequency and the presence of water column (red shiner; Cyprinella lutrensis) or grazing minnows (Phoxinus) on ecosystem processes, and (3) tested the effects of species loss from the grazer functional feeding group on stream ecosystem structure and function. I found that dace affected some aspects of ecosystem structure but not function, which suggested that grazer effects in prairie streams may not be consistent across taxa. In the context of flood frequency, both the water column omnivore and dace affected recovery of prairie stream primary producers following flooding disturbance by stimulating production, presumably through nutrient remineralization. However, some of these effects were transient or dependent on flood frequency, and my results indicate that consumer effects depend not only on environmental venue but also on the balance between consumptive losses and nutrient stimulation. In a comparison of the effects of removing different taxa from a grazer assemblage, the loss of crayfish, snails, or dace from a grazer assemblage did not differentially affect ecosystem processes, suggesting overlap in the ecosystem roles of these species in the context of this experiment.
Keywords: Biodiversity; Ecosystem function; Flood frequency; Grazing minnow; Omnivorous minnow; Prairie stream; Biology, Ecology (0329)